2022
DOI: 10.1371/journal.pone.0264849
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the gut microbiota composition of myostatin mutant cattle prepared using CRISPR/Cas9

Abstract: Myostatin (MSTN) negatively regulates muscle development and positively regulates metabolism through various pathways. Although MSTN function in cattle has been widely studied, the changes in the gut microbiota due to MSTN mutation, which contribute to host health by regulating its metabolism, remain unclear. Here, high-throughput sequencing of the 16S rRNA gene was conducted to analyze the gut microbiota of wild-type (WT) and MSTN mutant (MT) cattle. A total of 925 operational taxonomic units (OTUs) were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…Additionally, intestinal fungi are closely related to bacteria, and their stable antagonistic and mutually beneficial symbiosis is fundamental to the homeostatic balance of intestinal microorganisms. The present study previously detected bacterial communities in the MSTN mutant cattle and found that MSTN mutations affected the metabolism of the host by affecting the composition of the bacteria (10). However, knowledge of the characteristics of the gut fungal community composition in the MSTN mutation cattle is still limited.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Additionally, intestinal fungi are closely related to bacteria, and their stable antagonistic and mutually beneficial symbiosis is fundamental to the homeostatic balance of intestinal microorganisms. The present study previously detected bacterial communities in the MSTN mutant cattle and found that MSTN mutations affected the metabolism of the host by affecting the composition of the bacteria (10). However, knowledge of the characteristics of the gut fungal community composition in the MSTN mutation cattle is still limited.…”
Section: Discussionmentioning
confidence: 82%
“…The cattle used in the present study were presumably 24-month-old females raised as common beef cattle in a local ranch. Sample collection was performed as described in an earlier study ( 10 ). Total DNA was extracted from fecal samples using the QlAamp Fast DNA Stool Mini Kit (Qiagen, Germany) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that the gut microbiome has a synergistic effect on host growth and health. Previous studies have revealed a positive change of microbiota in pigs and cattle following mutation of the MSTN [ 20 , 21 ]. However, the effect of MSTN gene editing on the composition and function of gut microbiota in sheep is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Skeletal muscle growth is controlled by myostatin ( MSTN ), sometimes called growth and differentiation factor 8 [ 1 4 ]. It has been mapped to bovine chromosome 2 and is composed of three exons and two introns [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%